High V-PPase activity is beneficial under high salt loads, but detrimental without salinity - Graus, Dorothea; Patir, Meliha Gorkem; Schumacher, Karin (The new phytologist, 2018)
The membrane-bound proton-pumping pyrophosphatase (V-PPase), together with the V-type H+-ATPase, generates the proton motive force that drives vacuolar membrane solute transport. Transgenic plants constitutively overexpressing V-PPases were shown to have improved salinity tolerance, but the relative impact of increasing PPi hydrolysis and proton-pumping functions has yet to be dissected. For a better understanding of the molecular processes underlying V-PPase-dependent salt tolerance, we transiently overexpressed the pyrophosphate-driven proton pump (NbVHP) in Nicotiana benthamiana leaves and studied its functional properties in relation to salt treatment by primarily using patch-clamp, impalement electrodes and pH imaging. NbVHP overexpression led to higher vacuolar proton currents and vacuolar acidification. After 3 d in salt-untreated conditions, V-PPase-overexpressing leaves showed a drop in photosynthetic capacity, plasma membrane depolarization and eventual leaf necrosis. Salt, however, rescued NbVHP-hyperactive cells from cell death. Furthermore, a salt-induced rise in V-PPase but not of V-ATPase pump currents was detected in nontransformed plants. The results indicate that under normal growth conditions, plants need to regulate the V-PPase pump activity to avoid hyperactivity and its negative feedback on cell viability. Nonetheless, V-PPase proton pump function becomes increasingly important under salt stress for generating the pH gradient necessary for vacuolar proton-coupled Na+ sequestration.
Gesehen am 15.05.2019